Diagnóstico das espécies ativas do plasma usado em tratamentos termoquímicos do titânio - Barbosa, Julio Cesar Pereira (2011)
Plasma diagnostics by Optical Emission Spectroscopy were performed for electrical discharge in three gas mixture respecting the combinations z N2 y Ar x H2, z N2 y Ar x O2 e z N2 y Ar x CH4, in which the indexes z and y systematically vary from 1 to 4 and x varies from 0 to 4, every one has dimension SCCM, resulting in 80 combinations. From the all obtained spectrums, the species CH (387,1 nm), N2+ (391,4 nm), Hβ (486,1 nm), Hα (656,3 nm), Ar (750,4 nm), O (777,4 nm) e O (842,6 nm) were analyzed because of their abundance and importance on the kinetic of reaction from the plasma to surface, besides their high dependences on the gases flows. Particularly interesting z, y and x combinations were chosen in order to study the influence of active species on the surface modification during the thermochemical treatment. From the mixtures N2 Ar O2 e N2 Ar CH4 were chosen three peculiar proportions which presented luminous intensity profile with unexpected maximum or minimum values, denominated as plasma anomaly. Those plasma concentrations were utilized as atmosphere of titanium treatment maintaining constant the control parameters pressure and temperature. It has been verified a relation among luminous intensity associated to N2+ and roughness, nanohardness and O atoms diffusion into the crystalline lattice of treated titanium and it has been seen which those properties becomes more intense precisely in the higher points found in the optical profile associated to the N2+ specie. Those parameters were verified for the mixture which involved O2 gas. For the mixture which involves CH4 gas, the relation was determinate by roughness, number of nitrogen and carbon atoms diffused into the titanium structure which presented direct proportionality with the luminous intensity referent to the N2+ and CH. It has been yet studied the formation of TiCN phases on the surface which presented to be essentially directly proportional to the increasing of the CH specie and inversely proportional to the increasing of the specie N2+